The Effect of Fiscal Decentralization on Poverty Alleviation in Districts/Cities of Lampung Province in 2019–2024 - Fridhia Nabilla Zahra; M Rafly Darmawan; Hilya Imanina; Sevia Karmila Carles (Diponegoro Journal of Economics, 2025)
Nearly every developing country, including Indonesia, struggles with poverty. To address this issue, the government has established budgetary measures aimed at improving the effectiveness and independence of regional development. The objective of this research is to examine how fiscal decentralization affects poverty alleviation in districts and cities in Lampung Province from 2019 to 2024. The poverty rate serves as the dependent variable, while the independent variables consist of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH), and Regional Expenditure. Based on the results of the Chow and Hausman tests, the analytical approach employed is panel data regression using the Fixed Effect Model (FEM). The findings indicate that while the Revenue Sharing Fund (DBH) does not have a significant impact on poverty alleviation, PAD, DAU, DAK, and regional government expenditure significantly influence poverty reduction. With a coefficient of determination of 96.5%, all independent variables simultaneously have a significant impact on poverty alleviation. This study contributes to the empirical literature on fiscal decentralization by providing evidence on the effectiveness of regional fiscal instruments in reducing poverty at the district/city level in Lampung Province during the 2019–2024 period.